Diversão no tempo de trabalho: um estudo de caso sobre quem trabalha com entretenimento - Sendin, Victor Giovanetti (Universidade Federal de São Carlos, 2025)
This study aims to analyze the dynamics of work and leisure in the daily lives of a progressive metal cover/tribute band, identified as AE, located in the Campinas region, in the interior of São Paulo. The research focuses on the period from 2022 to 2024, following the musicians' daily practices, including moments of creation, rehearsal, and performance. The progressive metal genre was chosen as the object of analysis because it demands high technical competence and creative innovation, factors that make the study relevant within the context of musical entertainment. The study seeks to understand how the musicians of the AE band perceive and experience the intersection between work and leisure in their activities, investigating questions about the balance between professional demands and the fun inherent in the entertainment sector. Our work time and our leisure time are often treated as opposite and distinct dimensions, but for those who work providing leisure to the public, such as musicians and artists, this relationship can take on more complex characteristics. Are these professionals able to have fun at work, or do they see the activity as just another serious responsibility, similar to any other profession? Furthermore, this study aims to investigate whether these workers’ time is limited to the moments when they are entertaining the public, or whether there is a significant effort behind the scenes, involving preparation, planning and practice. To answer these questions, the study uses a qualitative and descriptive approach, based on case studies and participatory research. The research also considers the role of behind-the-scenes work, an element that is often invisible to the public. In addition to the performance, musicians dedicate hours to rehearsals, logistical organization, technical study of music and interaction with other professionals, activities that demonstrate the complexity of working in the entertainment sector. This study seeks to understand how these activities connect and contribute to the leisure and entertainment experience provided to the public, while also analyzing how musicians experience these responsibilities. Finally, this work aims to contribute to the understanding of the dynamics between work and leisure in the entertainment sector, with a focus on the progressive metal genre, a segment that combines artistic innovation and technical demands. By analyzing the experiences of the musicians of the band AE, we hope to broaden the discussion on the relationships between technical work, the playful aspect and the personal perception of professionals working in this field. This study offers a critical view on how work in the entertainment sector is articulated with the demands of creativity and social interaction, proposing reflections on the limits and intersections between fun and professional effort.
Fun at work: a case study of those who work in entertainment
Keywords: Entretenimento; Lazer; Trabalho; Shows; Metal-progressivo; Entertainment; Leisure; Work; Progressive metal; CIENCIAS SOCIAIS APLICADAS::TURISMO